Consumers' online purchasing intentions post COVID-19: Evidence from Lebanon and the Kingdom of Bahrain - Charbel M. El Khoury; Mrinalini Choudhary; Adel F. Al Alam (Administrative Sciences, 2023)
The future of consumers' online shopping trends post COVID-19 remains among the contemporary topics that necessitate further explorations. The aim of this research is to explore the intention of Lebanese and Bahraini consumers to shop online in the post pandemic era. This study extends the technology acceptance model that has exhibited prominent results when it comes of online purchasing. An online survey was addressed to consumers in Lebanon and the Kingdom of Bahrain to collect the data. More precisely, a total of 778 responses equally divided between the two countries was collected. Following the analysis of the data, it was found that both Lebanese and Bahraini shoppers demonstrate variations in the positive evidence associated with the elements of the technology acceptance model, except the perceived usefulness positive impact on consumers' intention toward online shopping where no significant impact was shown in both countries. Contactless payment modes have no significant impact on attitudes in both countries contrary to their positive impacts on the intention toward online shopping in both countries. The use of social media and price consciousness also have variations in the positive evidence linked to consumers attitudes in both countries. Finally, both the use of social media and price consciousness reveal differences in the level of negative association with consumers' intention toward online shopping in Lebanon and the Kingdom of Bahrain.
Keywords: 350; contactless payment; COVID-19; Kingdom of Bahrain; Lebanon; online shopping; price consciousness; social media usage; technology acceptance model